Childhood Arthritis and Rheumatology Research Alliance Consensus Treatment Plans for New‐Onset Polyarticular Juvenile Idiopathic Arthritis1. Issue 7 (July 2014) - Ringold, Sarah; Weiss, Pamela F.; Colbert, Robert A.; DeWitt, Esi Morgan; Lee, Tzielan; Onel, Karen; Prahalad, Sampath; Schneider, Rayfel; Shenoi, Susan; Vehe, Richard K.; Kimura, Yukiko; for the Juvenile Idiopathic Arthritis Research Committee of the Childhood Arthritis; et al.
<x xml:space="preserve">Abstract</x> Objective There is no standardized approach to the initial treatment of polyarticular juvenile idiopathic arthritis (JIA) among pediatric rheumatologists. Understanding the comparative effectiveness of the diverse therapeutic options available will result in better health outcomes for polyarticular JIA. The Childhood Arthritis and Rheumatology Research Alliance (CARRA) developed consensus treatment plans (CTPs) for use in clinical practice to facilitate such studies. Methods A case‐based survey was administered to CARRA members to identify the common treatment approaches for new‐onset polyarticular JIA. Two face‐to‐face consensus conferences employed modified nominal group technique to identify treatment strategies, operational case definition, end points, and data elements to be collected. A core workgroup reviewed the relevant literature, refined plans, and developed medication dosing and monitoring recommendations. Results The initial case‐based survey identified significant variability among treatment approaches for new‐onset polyarticular JIA. We developed 3 CTPs based on treatment strategies for the first 12 months of therapy, as well as case definitions and clinical and laboratory monitoring schedules. The CTPs include a step‐up plan (nonbiologic disease‐modifying antirheumatic drug [DMARD] followed by a biologic DMARD), an early combination plan (nonbiologic and biologic DMARD combined within a month of treatment initiation), and a biologic only plan. This approach was approved by 96% of the CARRA JIA Research Committee members attending the 2013 CARRA face‐to‐face meeting. Conclusion Three standardized CTPs were developed for new‐onset polyarticular JIA. Coupled with data collection at defined intervals, use of these CTPs will enable the study of their comparative effectiveness in an observational setting to optimize initial management of polyarticular JIA.